Uji Pendahuluan Anti-biofilm Esktrak Teh Hijau dan Teh Hitam Pada Streptococcus mutans melalui Metode Microtiter Plate: An initial study on anti-biofilm activity of green tea dan black tea extracts on Streptococcus mutans via mictotiter plate assay - Arjuna, Andi; Pratama, Winda Setya; Sartini, Sartini; Mufidah, Mufidah (Universitas Tadulako, 2018)
Tea (Camellia sinensis L.) has an activity as an antibacterial, widely studied to plankton cells, without further researching into biofilm cell. Therefore, this research had been conducted to initially evaluate the activity of green- and black-tea extracts in inhibiting Streptococcus mutans biofilm. Green and black tea leaves were extracted using 70% methanol. Determination of MIC was subsequently performed by microdilution method. Next, the biofilm formation and inhibition were run through microtiter plate method using flexible U-bottom PVC 96 wells, which then observed using microplate reader on Î» = 515 nm. As The results, MIC for green and black tea extract stood at 4 mg/mL, 6 mg/mL respectively. The biofilm inhibitory activity of black tea extract was at 8 and 10 mg/mL inhibiting 6 % and 12.5 % S. mutans. Green tea extract showed that concentration of 4 to 10 mg/mL was able to inhibit biofilm growth by 24%; 45%; 48% and 53%. Thus, through microtiter plate assay, it could be concluded that tea extract has potent antibiofilm to S. mutans, where green tea extract has better activity than black tea extract.